2020
DOI: 10.3390/ijerph17041451
|View full text |Cite
|
Sign up to set email alerts
|

Joint Toxicity of a Multi-Heavy Metal Mixture and Chemoprevention in Sprague Dawley Rats

Abstract: To explore the joint toxicity and bio-accumulation of multi-heavy metals and potential chemoprevention strategies, Male Sprague Dawley (SD) rats (n = 30) were treated orally once a week for six months with 500mg/kg•bw of eight heavy metals which were commonly identified in aquatic products in the Ningbo area including chromium, manganese, nickel, copper, zinc, cadmium, mercury, and lead. At the same time, 200mg/kg•bw of epigallocatechin-3-gallate (EGCG), trisodium citrate dihydrate (TCD) or glutathione (GSH) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 47 publications
0
11
0
2
Order By: Relevance
“…Administration of catechins hydrate modulated benzo(a)pyrene-induced apoptotic toxicity and inflammation by regulating the expression of TNF-a, NF-jB, COX-2, BAX and caspase-3 in mice lung tissue (Shahid et al, 2016). Wang et al (2020) reported that EGCG helps the excretion of various heavy metals, including Hg, Cd, Cr, Ni, and Cu, absorbed into the body and reduces toxicity in tissues. Catechins have a high binding affinity with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) proteins containing 3-chymotrypsin-like cysteine protease (3CL), RNA-dependent RNA polymerase (RdRp), and receptor-binding domain (RBD), so they have the potential to act as an excellent multi-targeting agent to regulate COVID-19 pandemic.…”
Section: Respiratory Disease and Inflammationmentioning
confidence: 99%
“…Administration of catechins hydrate modulated benzo(a)pyrene-induced apoptotic toxicity and inflammation by regulating the expression of TNF-a, NF-jB, COX-2, BAX and caspase-3 in mice lung tissue (Shahid et al, 2016). Wang et al (2020) reported that EGCG helps the excretion of various heavy metals, including Hg, Cd, Cr, Ni, and Cu, absorbed into the body and reduces toxicity in tissues. Catechins have a high binding affinity with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) proteins containing 3-chymotrypsin-like cysteine protease (3CL), RNA-dependent RNA polymerase (RdRp), and receptor-binding domain (RBD), so they have the potential to act as an excellent multi-targeting agent to regulate COVID-19 pandemic.…”
Section: Respiratory Disease and Inflammationmentioning
confidence: 99%
“…Mathematical methodologies have been developed to estimate the consequences of the combined effect of chemicals: These conceptual models are mainly based on the assumption of either additive or independent actions, and they have been used to predict the mixture toxicity and to obtain some insight on the mechanisms associated with metal mixture [67][68][69]. These mathematical models, however, have limited practical applications because of the assumption that there is no interaction among the components of the mixture and because it is difficult to consider the relevance of the different chemical speciation of each metal present in the mixture [70].…”
Section: In Vitro Effects Of a Metal Mixturementioning
confidence: 99%
“…The conditions for the digestion of MARS 6 classic were as follows: up to 180 • C for 25 min and then constant for 20 min, followed by a cooling stage (30 min) at 80 • C. Digested samples were diluted with ultrapure water after cooling to room temperature. These samples were used for the final heavy-metal element analysis, performed with an ICP-MS equipped with a concentric Nebulizer, a quartz torch with a quartz injector tube, and a cyclonic spray chamber [55].…”
Section: Molecular Analysismentioning
confidence: 99%